A significant decrease in D-dimer concentration within one month of anticoagulation therapy as a predictor of both complete recanalization and risk of recurrence after initial pulmonary embolism. Issue 202 (June 2021) - Aranda, Carlos; Peralta, Luisa; Gagliardi, Lidia; López, Alberto; Jiménez, Ángel; Herreros, Benjamín
Abstract: Background: Abnormal D-dimer concentration measured during anticoagulation therapy (AT) or within one month of discontinuation, is associated with residual pulmonary obstruction (RPO) and risk of recurrent venous thromboembolism (VTE) after a first episode of pulmonary embolism (PE). We hypothesized that a significant decrease in D-dimer concentration within the first month of AT in patients with a first episode of PE may predict complete recanalization and a lower risk of recurrent VTE. Methods: One hundred and fifty patients with PE received anticoagulation therapy for three or six months when control computed tomography angiography (CTA) was performed. D-dimer levels were measured at admission and at 1-, 3- and/or 6-month follow-ups after the initial event. Clinical, echocardiographic, CTA and analytical data were collected. Predictive factors of RPO and predictive ability of D-dimer concentration at 1- and 6-month follow-ups were evaluated. Results: Of the 150 eligible patients, 33 (22%) had RPO in control CTA. Idiopathic PE, a delay of >7 days between symptom onset and diagnosis, and clinical PE severity determined by a s-PESI score ≥ 1 were associated with RPO. D-dimer concentration within a month of AT was significantly higher (823 [558–1259] vs 436 [243–934] ng/ml; p = 0.019) in patients with RPO; decrease (445 [35–1899] vs 912 [476–2858] ng/ml; p = 0.047) and decrease percentage (31.4% vs 76.6%; p < 0.005) in D-dimer concentrations were significantly lower. ROC analysis showed that decrease percentage in D-dimer concentration identified patients with complete recanalization (AUC 0.715, [95% CI, 0.611–0.819], p < 0.005). Decreases of >70% in initial D-dimer at 1-month (OR, 0.56, [95% CI, 0.45–0.70] p = 0.037) and 6-month follow-ups (OR, 0.31 [CI 95%, 0.15–0.66], p = 0.03) were associated with a lower risk of recurrent PE. Conclusion: A significant decrease in D-dimer concentration within the first month of AT is associated with complete recanalization and could predict a lower risk of recurrent thrombosis after a first episode of PE. Highlights: Providing evidence on complete resolution after a first pulmonary embolism. We identify three independent risk factors of residual pulmonary obstruction (RPO). Absence of RPO can be predicted within the first month of anticoagulation therapy. Significant decrease in D-dimer concentration is associated with complete recanalization. Could predict a lower risk of recurrent thrombosis.